Case Series on Chiasmal Lesions with Ocular Manifestations seen at the Eye Center of a Tertiary Government Hospital in Philippines - Aishath, Jeneena Amir; Lourdes, Ang (Journal of Ophthalmic Science, 2020)
Objective To identify common ocular and non-ocular signs and symptoms of patients with chiasmal lesions presenting to ophthalmologists.  Methods This is a three year case series of patients who presented to Rizal Medical Center Ophthalmology OPD clinic, diagnosed as cases of chiasmal lesion with a complete neuro-ophthalmogical exam, ancillary test and neuroimaging. Data collected include patient profile, ocular and non ocular symptoms, duration of blurring of vision (BOV), best corrected visual acuity (BCVA), Color Vision, Optic nerve (ON) description, Visual field defects (VFD) and size & location of chiasmal lesion.  Results A total of twelve patients were included with 1:1 M:F ratio and a median age of 39 years. Blurring of Vision was the presenting symptom in 10 cases, bulging of the eyes and headaches in the remaining cases. Associated symptoms include: non specific headache in all; diplopia in 3 (1 with and 2 without motility defects); and systemic symptoms related to hormonal imbalance in 2 cases. Best corrected vision ranged from 6/6 to no light perception (NLP). Color vision was affected in all cases. ON palor was seen in 6 (50%) and disc edema in 1 case. VFD include Junctional scotoma (58.33%), bitemporal hemianopia (33.3%) and generalised scotoma (8.3%). Neuroimaging revealed pituitary lesions in 10 cases, 1 craniopharyngioma and ON glioma with chiasmal extension. Conclusion Ocular and non ocular symptoms seen were comparable to other studies except that Junctional scotoma was the most common VFD identified in the included population of our case series. This highlights the importance of VF testing among patients complaining of unilateral visual loss to rule out a chiasmal lesion.
Keywords: Chiasmal lesions; pituitary adenoma; Bitemporal Hemianopsia; junctional scotoma